2018
DOI: 10.1667/rr15023.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Research in Radiation Oncology through Interdisciplinary Collaboration

Abstract: The contribution of radiation oncology to the future of cancer treatment depends significantly on our continued clinical progress and future research advancements. Such progress relies on multidisciplinary collaboration among radiation oncologists, medical physicists and radiobiologists. Cultivating collaborative educational and research opportunities among these three disciplines and further investing in the infrastructure used to train both clinicians and researchers will therefore help us improve the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…New visionary roads are needed to optimally address the grand challenges of our times and of the coming future. A common message, largely present in all four challenges, is that the field of medical physics should accelerate toward multidisciplinarity [3,4,[69][70][71], with different problems and unexplored fields to be explored. This is connected with the intrinsic translational nature of medical physics but also contains something new, mostly linked to the rapid evolution toward personalized medicine, stressing the growing need of hybridization.…”
Section: Leadership In the Changing World Of Radiation Oncologymentioning
confidence: 99%
“…New visionary roads are needed to optimally address the grand challenges of our times and of the coming future. A common message, largely present in all four challenges, is that the field of medical physics should accelerate toward multidisciplinarity [3,4,[69][70][71], with different problems and unexplored fields to be explored. This is connected with the intrinsic translational nature of medical physics but also contains something new, mostly linked to the rapid evolution toward personalized medicine, stressing the growing need of hybridization.…”
Section: Leadership In the Changing World Of Radiation Oncologymentioning
confidence: 99%
“…They also bring diversity to the research pool and we all know diversity is what fuels progress and advancement. By mandating research as part of MOC will additionally encourage physicists to seek more collaboration with other centers which will result in positive outcomes 7 …”
Section: For the Proposition: Christopher F Njeh Phdmentioning
confidence: 99%
“…By mandating research as part of MOC will additionally encourage physicists to seek more collaboration with other centers which will result in positive outcomes. 7 It is often argued that the lack of protected research time and not enough staff is a hindrance for clinical medical physicists to do research. [8][9][10] However, if research, presentations and publications are required for MOC, employers will be more willing to provide time and resources to do research.…”
mentioning
confidence: 99%
“…As a result, discussion of controversies or changes in practice within radiation oncology involves input from all three disciplines. For this reason, significant effort has been expended recently to foster collaborative multidisciplinary research in radiation oncology, with substantial demonstrated benefit . In light of these results, we endeavor here to adopt this “team‐science” approach to the traditional debates featured in this journal.…”
Section: Three Discipline Collaborative Radiation Therapy (3dcrt) Debmentioning
confidence: 99%